Supply disruptions and regional price effects in a spatial oligopoly - an application to the global gas market - Christian Growitsch; Harald Hecking; Timo Panke (Institute of Energy Economics at the University of Cologne (EWI), 2013)
Supply shocks in the global gas market might affect countries differently since the market is regionally interlinked but not perfectly integrated. Additionally, high supply side concentration might expose countries to market power in different ways. To evaluate the strategic position of importing countries concerning gas supplies we disentangle import prices to price increasing and decreasing factors. Since the interrelations on the global gas market are complex we use an equilibrium model programmed as a mixed complementarity problem (MCP) and simulate the blockage of LNG flows through the Strait of Hormuz. This enables us account for the oligopolistic nature and the asymmetry of the gas supply side. We fi nd that Japan faces the most severe price increases as it completely relies on LNG supply. In contrast, European countries like the UK bene fit from a good interconnection to the continental pipeline system and significant domestic price-taking production, both of which help to mitigate an increase in physical costs of supply as well as the exercise of market power.
Keywords: C61; L72; Q34; Q41; 330; Natural gas market; security of supply; international trade; mixed complementarity problem